Tri‐polarised antenna – a virtual rotatable dual‐polarised antenna used in polarised beampattern synthesis. Issue 14 (1st November 2015) - Hu, Wanqiu; Li, Yongzhen; Li, Mianquan; Chen, Siwei; Wang, Xuesong; Xiao, Shunping
Abstract : Tri‐polarised antennas are exploited to synthesise the optimal polarised beampattern in this study. First, the characteristics of a single tri‐polarised antenna are studied with an infinite current sheet model. Using the cross‐product algorithm, the authors find that three co‐located orthogonal current sheets are equivalent to a pair of orthogonal current sheets in a particular orientation. It implies that the tri‐polarised antenna is just virtually equivalent to a rotatable dual‐polarised antenna. Then by formulating the problem in a convex form, they adopt the convex optimisation algorithm to synthesise optimal polarised beampattern of the tri‐polarised array. The simulation results show that due to the increased orientation degree of freedom, the sidelobe and cross‐polarisation level of tri‐polarised array are significantly lower than the dual‐polarised array.